Validation of the Interpersonal Forgiveness Indonesian Scale: An examination of its psychometric properties using confirmatory factor analysis - Yusuf, Gilang Tri Prayogo; Şimşek, Ahmet Salih; Setiawati, Farida Agus; Tiwari, Gyanesh Kumar; Kianimoghadam, Amir Sam (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2024)
In recent years, research has highlighted the essential role of forgiveness in fostering interpersonal relationships and preserving social harmony. However, more precise measurement methods are necessary, particularly in the Indonesian context. The purpose of this study was to develop the Interpersonal Forgiveness Indonesian Scale. The investigation rigorously explores the construct by implementing confirmatory factor analysis. To evaluate the instrument's reliability, we used McDonald's omega coefficient. This study included 549 adults aged 18 to 35 from Yogyakarta, with a mean age of 23.09, including 258 males and 291 females. The loading values for revenge and avoidance factors were .724 to .841 and .796 to .845, respectively; while benevolence varied more, ranging from .538 to .824. The McDonald's omega value of .953 indicated excellent reliability. Robust correlations between the items and factors on the Interpersonal Forgiveness Indonesian Scale demonstrate its effectiveness and relevance in Indonesia. Future research should explore the dynamics of interpersonal forgiveness across diverse regions in Indonesia to gain a better understanding of the phenomenon within distinct cultural contexts.